Evolutionary Transcriptomics and Proteomics: Insight into Plant Adaptation. (June 2017) - Voelckel, Claudia; Gruenheit, Nicole; Lockhart, Peter
Abstract : Comparative transcriptomics and proteomics (T&P) have brought biological insight into development, gene function, and physiological stress responses. However, RNA-seq and high-throughput proteomics remain underutilised in studies of plant adaptation. These methodologies have created discovery tools with the potential to significantly advance our understanding of adaptive diversification. We outline experimental recommendations for their application. We discuss analysis models and approaches that accelerate the identification of adaptive gene sets and integrate transcriptome, proteome, phenotypic, and environmental data. Finally, we encourage widespread uptake and future developments in T&P that will advance our understanding of evolution and adaptation. Trends: Difficulties in making progress working at the level of the genome in plant adaptation studies have prompted investigations of alternative omics approaches. High-throughput technologies have advanced to provide high-quality information on the identification and abundance of RNA and proteins in plant tissues. Recent attention has focused on analytical methods that identify genes and proteins exhibiting expression patterns that are anomalous with respect to stochastic expectations. It is thought that such genes and proteins maybe linked to traits of adaptive significance. Researchers report that methodology for the study of gene and protein expression levels, if cautiously applied, can be informative with both cultivated and natural populations. This realisation has led to investigations of differences in cryptic traits for physiology/metabolism and the evolution of some of their genetic determinants.